PENGARUH LINGKUNGAN KELUARGA DAN KEPRIBADIAN WIRAUSAHATERHADAP KEBERHASILAN USAHA PADA USAHA KECIL DI SURABAYA: (Studi Kasus pada Pelaku Usaha di Sentra Kuliner Convention Hall jalan Gebang Putih Surabaya) - Amalia Lutfa Tunida (KELOMPOK KOMUNITAS LABORATORIUM PENELITIAN, 2022)
Business success is a goal for each entrepreneur or business actor, with business success it can be said that the running of a business is successful and can achieve its goals. The purpose of this study is so determine the effect of Family Environment and Entrepreneurial Personality on Bussiness Success in small businesses in Surabaya (a case study at the Convention Hall Culinary center, Jalan Gebang Putih Surabaya). The scope used in this research is business actors at the Convention Center Culinary Center Hall Jalan Gebang Putih Surabaya. The method of data collection in this study is the questionnaire. To facilitate data collection, techniques are needed in making questionanaires that will be distributed to respondents. In completing this research, the data collection technique used is a data collection technique with a linkert scale which is a psychometric scale in research. The regression coefficient for the Family Environment variable is positive, indicating that there is an influene from the X1 variable. The regression coefficient of the Entrepreneurial Personality variable is positive, indicating that there is an influence from the X2 variable. The results of this study indicate that the two independent variables have an influence on the dependent variable when tested simultaneously.